Metode Topi Anatomi dan Fisiologi dalam Meningkatkan Kognitif Mahasiswa Keperawatan - Gatot Suparmanto; Sutiyo Dani Saputro (FORIKES, 2024)
Anatomy and physiology courses are basic courses in the health sector that study body anatomy and the function of organ systems down to the cellular level. Anatomy and physiology courses are also mandatory courses for undergraduate nursing students. Along the way, anatomy and physiology courses have become difficult or difficult courses for students because understanding these courses requires a lot of time and effort, because they require the process of memorizing and also understanding the many functions of the human body. The academic report in the form of student grades in the anatomy and physiology course in 2019 for undergraduate nursing students at Kusuma Husada University before improvement was 55 and this result is still below the passing threshold, namely 64. So a more innovative approach is needed, namely using the learning method